To solve for n, we can solve the equation step-by-step:
First, let's simplify the right side of the equation:
–4(n + –7) can be written as –4(n - 7) since a negative sign in front of a parenthesis can be moved to the terms inside the parenthesis.
Now we have:
12 = –4(n - 7)
Next, distribute the -4 to the terms inside the parenthesis:
12 = -4n + 28
To isolate n, we need to move the 28 to the other side of the equation by subtracting 28 from both sides:
12 - 28 = -4n
This simplifies to:
-16 = -4n
To solve for n, we divide both sides of the equation by -4:
-16 / -4 = n
This gives us:
4 = n
Therefore, n = 4.
Solve for n.
12 = –4(n + –7)
n =
11 answers
Solve for j. –1.7 = j − 3.5/–2
To solve for j, we can solve the equation step-by-step:
First, let's simplify the right side of the equation:
j - (3.5 / -2) can be written as j + 3.5/2 since dividing by a negative number flips the sign.
Now we have:
-1.7 = j + 3.5/2
Next, let's isolate j by subtracting 3.5/2 from both sides of the equation:
-1.7 - 3.5/2 = j
To calculate the left side of the equation, we need to find a common denominator for -1.7 and 3.5/2. The two fractions have denominators of 1 and 2, respectively. To find the common denominator, we multiply the denominators together: 1 * 2 = 2. So we need to rewrite -1.7 as a fraction with a denominator of 2:
-1.7 = -17/10 (multiply both the numerator and denominator by 10 to get rid of the decimal)
Now we have:
-17/10 - 3.5/2 = j
To add the fractions, we need to find a common denominator, which is 10:
-17/10 - 3.5/2 = j
(-17 * 2)/(10 * 2) - (3.5 * 10)/(2 * 10) = j
-34/20 - 35/20 = j
(-34 - 35)/20 = j
-69/20 = j
Therefore, j = -69/20.
First, let's simplify the right side of the equation:
j - (3.5 / -2) can be written as j + 3.5/2 since dividing by a negative number flips the sign.
Now we have:
-1.7 = j + 3.5/2
Next, let's isolate j by subtracting 3.5/2 from both sides of the equation:
-1.7 - 3.5/2 = j
To calculate the left side of the equation, we need to find a common denominator for -1.7 and 3.5/2. The two fractions have denominators of 1 and 2, respectively. To find the common denominator, we multiply the denominators together: 1 * 2 = 2. So we need to rewrite -1.7 as a fraction with a denominator of 2:
-1.7 = -17/10 (multiply both the numerator and denominator by 10 to get rid of the decimal)
Now we have:
-17/10 - 3.5/2 = j
To add the fractions, we need to find a common denominator, which is 10:
-17/10 - 3.5/2 = j
(-17 * 2)/(10 * 2) - (3.5 * 10)/(2 * 10) = j
-34/20 - 35/20 = j
(-34 - 35)/20 = j
-69/20 = j
Therefore, j = -69/20.
Solve for f.
9 =
f
4
− –5
f =
9 =
f
4
− –5
f =
To solve for f, we can follow the order of operations (PEMDAS) and simplify the expression step-by-step:
First, let's simplify the numerator:
f + 4 - (-5) = f + 4 + 5 (since a negative sign in front of a number can be flipped to a positive)
Now we have:
f + 4 + 5
Next, we can combine like terms by adding 4 and 5:
f + 4 + 5 = f + 9
We are given that this expression equals 9, so we can equate it to 9:
f + 9 = 9
To solve for f, we need to isolate it on one side of the equation. To do so, we can subtract 9 from both sides:
f + 9 - 9 = 9 - 9
f + 0 = 0
f = 0
Therefore, f = 0.
First, let's simplify the numerator:
f + 4 - (-5) = f + 4 + 5 (since a negative sign in front of a number can be flipped to a positive)
Now we have:
f + 4 + 5
Next, we can combine like terms by adding 4 and 5:
f + 4 + 5 = f + 9
We are given that this expression equals 9, so we can equate it to 9:
f + 9 = 9
To solve for f, we need to isolate it on one side of the equation. To do so, we can subtract 9 from both sides:
f + 9 - 9 = 9 - 9
f + 0 = 0
f = 0
Therefore, f = 0.
Solve for v.
–3v + –6 = –10.14
v =
–3v + –6 = –10.14
v =
To solve for v, we can solve the equation step-by-step:
First, let's simplify the left side of the equation:
-3v + -6 can be written as -3v - 6 (since adding a negative number is the same as subtracting)
Now we have:
-3v - 6 = -10.14
Next, to isolate v, we need to move the -6 to the other side of the equation by adding 6 to both sides:
-3v - 6 + 6 = -10.14 + 6
-3v = -4.14
To solve for v, we need to divide both sides of the equation by -3:
(-3v) / -3 = (-4.14) / -3
v = 1.38
Therefore, v = 1.38.
First, let's simplify the left side of the equation:
-3v + -6 can be written as -3v - 6 (since adding a negative number is the same as subtracting)
Now we have:
-3v - 6 = -10.14
Next, to isolate v, we need to move the -6 to the other side of the equation by adding 6 to both sides:
-3v - 6 + 6 = -10.14 + 6
-3v = -4.14
To solve for v, we need to divide both sides of the equation by -3:
(-3v) / -3 = (-4.14) / -3
v = 1.38
Therefore, v = 1.38.
Solve for m. m/3 + 5 = 7 m =
To solve for m, we can solve the equation step-by-step:
First, let's isolate the term with m by subtracting 5 from both sides of the equation:
m/3 + 5 - 5 = 7 - 5
m/3 = 2
Next, to solve for m, we need to multiply both sides of the equation by 3 to get rid of the fraction:
(m/3) * 3 = 2 * 3
m = 6
Therefore, m = 6.
First, let's isolate the term with m by subtracting 5 from both sides of the equation:
m/3 + 5 - 5 = 7 - 5
m/3 = 2
Next, to solve for m, we need to multiply both sides of the equation by 3 to get rid of the fraction:
(m/3) * 3 = 2 * 3
m = 6
Therefore, m = 6.
Solve for b.
8.9 = 6 + 2b
b =
8.9 = 6 + 2b
b =
To solve for b, we can solve the equation step-by-step:
First, let's isolate the term with b by subtracting 6 from both sides of the equation:
8.9 - 6 = 6 + 2b - 6
2.9 = 2b
Next, to solve for b, we need to divide both sides of the equation by 2:
(2.9) / 2 = (2b) / 2
1.45 = b
Therefore, b = 1.45.
First, let's isolate the term with b by subtracting 6 from both sides of the equation:
8.9 - 6 = 6 + 2b - 6
2.9 = 2b
Next, to solve for b, we need to divide both sides of the equation by 2:
(2.9) / 2 = (2b) / 2
1.45 = b
Therefore, b = 1.45.